Simultaneous fine structure observation of wind and temperature profiles by the Arecibo 430-MHz radar and in situ measurements - Thomas, D. (1986)
The study of the interaction between waves and turbulence in the troposphere and lower stratosphere requires continuous fine structure observation of both wind and temperature profiles. The radar technics (ST radar) allow a continuous observation of wind profiles with a vertical resolution of at least 150 m, while balloon-borne me measurements of temperature and wind are potentially able to provide a spatial resolution as short as 0.1 m along the balloon trajectory. The use of balloon-borne technics, concurrently with radar observational, is necessary to understand the generation mechanisms of turbulence and to improve our knowledge about the radar measurement physics FRITTS et al., 1984; THOMAS et al., 1985).